Perceptions of potential employees on teleworking in private firms in Kuala Lumpur - Kadar Hamsa, Abdul Azeez (Research Centre, International Islamic University Malaysia, 2006)
Teleworking or telecommuting is relatively a new subject, slowly gaining the attention of various parties, especially those in the labour sectors. Teleworking is an option worth considering because of the flexibility it provides and reduction in commute trips. However, this new work option has yet to penetrate the business environment throughout the nation. Reported research on this topic is still very limited, confined mostly to perceptual and prevalence studies. This study investigates the perceptions of potential employees towards teleworking. It focuses on four main areas; demographic characteristics, basic travel characteristics, perceptions on the advancement of ICT and perceptions on teleworking. The main finding from this study is that 81% of the respondents were willing to practice teleworking of their organizations offer them such option. Other findings favouring teleworking include: reduction in travel cost, time and stress, more time with family and increased flexibility.